DIGITALIZATION OF HALAL PRODUCT BUSINESS FOR BUSINESS ACTORS ASSISTED BY BPR SYARIAH AMANAH RABBANIAH - Nurfahmiyati; Rahmani, Annisa Nadiyah; Nurcholisah, Kania; Notolegowo, Hantoro Ksaid; Azan, Ferdi Zanuar; Nurhayati, Nunung (UPT Publikasi Ilmiah UNISBA, 2024)
MSMEs play an important role in the Indonesian economy, and many have utilized information technology to market Halal products. BPR Syariah Amanah aims to help MSMEs by providing business funds. There are problems that often occur, namely the lack of understanding and knowledge about the digitalization of halal product businesses, limited funds for advertising on social media (Instagram Ads and Google Ads), and the lack of skills in creating advertising content and reports on the realization of advertising on social media. The purpose of this study is to provide an understanding of halal product business digitalization training through Instagram ads, creating Gojek accounts for business actors, creating business WhatsApp, and creating content on Canva. The methods used in this study are lecture methods, discussion methods, and simulation methods. The results of community service activities provide a score increase of 17.14% in the level of understanding of participants in business digitalization training. This means that the training provides changes in understanding the application of business digitalization for MSMEs. Keywords : Business Digitalization, Halal Products, MSME